Avaliação da política pública de atendimento educacional especializado (AEE) do município de Aquiraz - Pinto, Maria Erlice Setúbal (2025)
The National Policy on Special Education from the Perspective of Inclusive Education (PNEEPEI/2008) stands as a milestone in Brazilian education by promoting access for students with disabilities to regular schools and assigning the responsibility for Specialized Educational Services (AEE) to educational institutions. This policy aims to ensure the constitutional right to inclusive education and foster equal opportunities, aligning with the principles of accessibility and respect for diversity. The central objective of this study is to evaluate the National Policy on Special Education in the municipality of Aquiraz, Ceará, focusing on Specialized Educational Services (AEE) from its implementation to the present day. The methodology employs a qualitative approach, including field research, interviews, and entries in a field diary as data collection techniques, with participant observation. The target audience for this investigation includes regular classroom teachers, AEE teachers, school administrators, and family members of students with disabilities. The evaluative perspective adopted is In-Depth Evaluation, based on the counter-hegemonic evaluation framework proposed by Rodrigues (2008) and Lejano (2012). For the research methodology, strategies and data collection techniques are defined, adopting Bardin's (1994) content analysis. The study is informed by the literature of Martins (2015), Bezerra and Araújo (2014), Kassar (2012; 2016), Rabelo (2016), Candau (2012), Minayo (2002), Mantoan (2008), Saviani (2008), Sassaki (2015), among other scholars in this field. The results indicate significant progress, such as the increase in the number of multifunctional resource rooms and growing adherence to AEE. However, challenges remain, including the need for continuous teacher training, transparency in the implementation of individualized education plans (PEI), and the eradication of discrimination in the school environment. The research underscores the importance of collaboration among educational agents and the recognition of diversity as a fundamental value to strengthen school inclusion. It concludes that overcoming existing gaps requires investments in effective public policies and strategies that guarantee the comprehensive development of students with disabilities in the municipality.